Nghiên cứu độ bền bức xạ tử ngoại, nhiệt ẩm của một số màng phủ trên cơ sở nhựa acrylic. II – Nghiên cứu ảnh hưởng của bản chất và hàm lượng hệ ổn định quang đến độ bền bức xạ tử ngoại, nhiệt ẩm của màng phủ trên cơ sở nhựa acrylic polyol HSU 1168 khâu mạ - Hiền, Lê Xuân; Vương, Nguyễn Thiên; Việt Triều, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The influence of the chemical nature and content of some light stabilization systems based on ultraviolet radiation absorbers (UVA) TINUVIN T 1130, T 384 and hindered- amine light stabilizers (HALS) TINUVIN T 292 on the humid heat, ultraviolet radiation durability of the coatings based on acrylic polyol HSU 1168 crosslinked by polyisocyanate Desmodur N-75 have been studied. The effect of the light stabilizations systems has been evaluated. Their optimal contents in the coatings have been determined.